MAKNA GAYA BAHASA SYAIR LAGU PERJUANGAN INDONESIA PENDEKATAN TEKS DALAM KONTEKS SEJARAH - H.P., F.X. Nugroho (Department of Drama, Dance, and Musik (Sendratasik), Semarang State University, 2012)
This research was done by comparing the texts of the three types of poems, then interpreting the meanings of nationalism according to them. Especially, the message of the language styles of the national song lyrics: Indonesia Raya, Bagimu Negeri, Bhineka Tunggal Ika, Pada Pahlawan, and Bangun Pemudi Pemuda, is analyzed symbolically or poetically in the context of nationalism. From this research, some conclusions or results can be drawn. First, colonialism produces nationalism. Second, the poem Tanah Air expresses romantic nationalism which only admires the natural beauty of Sumatra. Third, the poem Aku reveals realistic nationalism which is based on the real resistance of the Indonesian people to expel the colonialist from Indonesia and reach the Independence of the Indonesian people. Fourth, the song lyrics: Indonesia Raya, Bagimu Negeri, Bhineka Tunggal Ika, Pada Pahlawan, and Bangun Pemudi Pemuda communicates human nationalism which asks the whole Indonesian people to do the best for the welfare of the whole Indonesian people and country. All language styles of the song lyrics are stuck on and signify the meaning of the human nationalism.ÃÂ This research was done by comparing the texts of the three types of poems, then interpreting the meanings of nationalism according to them. Especially, the message of the language styles of the national song lyrics: Indonesia Raya, Bagimu Negeri, Bhineka Tunggal Ika, Pada Pahlawan, and Bangun Pemudi Pemuda, is analyzed symbolically or poetically in the context of nationalism. From this research, some conclusions or results can be drawn. First, colonialism produces nationalism. Second, the poem Tanah Air expresses romantic nationalism which only admires the natural beauty of Sumatra. Third, the poem Aku reveals realistic nationalism which is based on the real resistance of the Indonesian people to expel the colonialist from Indonesia and reach the Independence of the Indonesian people. Fourth, the song lyrics: Indonesia Raya, Bagimu Negeri, Bhineka Tunggal Ika, Pada Pahlawan, and Bangun Pemudi Pemuda communicate human nationalism which asks the whole Indonesian peopleto do the best for the welfare of the whole Indonesian people and country. All language styles of the song lyrics are stuck on and signify the meaning of the human nationalism.